Penggunaan Media Liveworksheet Untuk Peningkatan Partisipasi Aktif Dalam Pembelajaran Tematik di SD Kelas Tinggi - Alfiana Shinta Putri; Ghefira Syahrani Putri; Nesya Priyandita (Program Studi PGSD Kampus UPI di Serang, 2021)
Learning for elementary school level with interactive learning model has started to be discussed by education experts in Indonesia recently. It started when Covid19 was rampant in Indonesia, which caused many schools to be closed to prevent the spread of COVID-19. Many elementary school teachers have lost their role and made many elementary school students lazy to do online learning at home and that made many teachers think about how to get elementary school students interested in learning even if only online. Finally, many teachers create interactive teaching and learning methods that can make students interested in learning again. Interactive learning is an interaction between students and students or students and teachers to analyze, solve problems, explore or discuss certain topics or problems. Interactive learning using live worksheet media for grade 4 elementary school children can be tested whether it can increase the participation of elementary school children or not in learning. Liveworksheet itself is an application that can be used to create interactive online materials and Student Worksheets (LKPD). The Ministry of National Education (Darusman, 2008:17) states that LKPD is a sheet that contains guidelines for students to carry out programmed activities. Where schools can facilitate students to use these media. active participation